Effect of amino acid‐based formula added to four‐food elimination in adult eosinophilic esophagitis patients: A randomized clinical trial. Issue 7 (18th November 2021) - de Rooij, Willemijn E.; Vlieg – Boerstra, Berber; Warners, Marijn J.; Van Ampting, Marleen T.J.; van Esch, Betty C. A. M.; Eussen, Simone R. B. M.; Bredenoord, Albert J.
Abstract: Background: Elimination of key foods restricts dietary options in eosinophilic esophagitis (EoE) patients. Addition of amino acid‐based formula (AAF) to an elimination diet might facilitate adherence and, therefore, enhance efficacy of dietary management. Aim: To evaluate whether addition of AAF to a four‐food elimination diet (FFED) is more effective than FFED alone in decreasing eosinophilia, endoscopic signs, and clinical outcomes. Methods: This randomized controlled trial enrolled 41 adult patients with active EoE (≥15 eosinophils (eos) per high power field (hpf)) at baseline biopsy. Subjects were randomized (1:1 ratio) to groups given a FFED or FFED with addition of AAF providing 30% of their daily energy needs (FFED + AAF). Histological disease activity, endoscopic signs, symptoms, and disease‐related quality of life (EoEQoL) were measured at baseline and after 6 weeks of intervention. Results: Patients (60% male, age 34.5 (interquartile range (IQR) 29–42.8 years)) were randomized to FFED ( n  = 20) or FFED + AAF ( n  = 21); 40 participants completed the diet. Complete histological remission (<15 eos/hpf) was achieved in 48% of FFED + AAF subjects ( n  = 21) vs. 25% of FFED subjects ( n  = 20), respectively ( p  = 0.204). Peak eosinophil counts (PEC) decreased significantly in both groups between baseline and week 6, but the change in PEC between groups was not different ( p  = 0.130). A significant but similar endoscopic and symptomatic reduction was observed in both groups (all; p <0.05). Total EoEQoL scores significantly improved in the FFED + AAF group between baseline and week 6 ( p  = 0.007), and not in the FFED group. Conclusion: The addition of AAF to a FFED did not lead to a larger decrease in PEC between baseline and 6 weeks, but may result in a significant improvement of QoL in adult EoE patients NL6014 (NTR6778). Abstract : A randomized clinical trial to investigate the effect of amino acid‐based formula added to four‐food elimination in adult eosinophilic esophagitis patients.